Co-expression of the SARS-CoV-2 entry receptors ACE2 and TMPRSS2 in healthy human conjunctiva. (April 2021) - Mencucci, Rita; Favuzza, Eleonora; Becatti, Matteo; Tani, Alessia; Mazzantini, Costanza; Vignapiano, Roberto; Fiorillo, Claudia; Pellegrini-Giampietro, DomenicoE.; Manetti, Mirko; Marini, Mirca; Landucci, Elisa
Abstract: The purpose of this study was to evaluate the expression of the SARS-CoV-2 receptors ACE2 and TMPRSS2 in an immortalized human conjunctival epithelial cell line and in healthy human conjunctiva excised during ocular surgery, using Western blot, confocal microscopy and immunohistochemistry. The Western blot showed that ACE2 and TMPRSS2 proteins were expressed in human immortalized conjunctival cells, and this was confirmed by confocal microscopy images, that demonstrated a marked cellular expression of the viral receptors and their co-localization on the cell membranes. Healthy conjunctival samples from 11 adult patients were excised during retinal detachment surgery. We found the expression of ACE2 and TMPRSS2 in all the conjunctival surgical specimens analyzed and their co-localization in the superficial conjunctival epithelium. The ACE2 Western blot levels and immunofluorescence staining for ACE2 were variable among specimens. These results suggest the susceptibility of the conjunctival epithelium to SARS-CoV-2 infection, even though with a possible interindividual variability.